Overactivation of the nuclear factor (erythroid‐derived 2)–like 2–antioxidant response element pathway in hepatocytes decreases hepatic ischemia/reperfusion injury in mice. Issue 1 (January 2016) - Lee, Lung‐Yi; Harberg, Calvin; Matkowskyj, Kristina A.; Cook, Shelly; Roenneburg, Drew; Werner, Sabine; Johnson, Jeffrey; Foley, David P.
Abstract : Hepatic ischemia/reperfusion injury (IRI) is a critical component of hepatic surgery. Oxidative stress has long been implicated as a key player in IRI. In this study, we examine the cell‐specific role of the nuclear factor (erythroid‐derived 2)–like 2 (Nrf2)–antioxidant response element pathway in warm hepatic IRI. Nrf2 knockout (KO) and wild‐type (WT) animals and novel transgenic mice expressing a constitutively active nuclear factor (erythroid‐derived 2)–like 2 (caNrf2) mutant in hepatocytes (AlbCre+/caNrf2+) and their littermate controls underwent partial hepatic ischemia or sham surgery. The animals were killed 6 hours after reperfusion, and their serum and tissue were collected for analysis. As compared to WT animals after ischemia/reperfusion (IR), Nrf2 KO mice had increased hepatocellular injury with increased serum alanine aminotransferase and aspartate aminotransferase, Suzuki score, apoptosis, an increased inflammatory infiltrate, and enhanced inflammatory cytokine expression. On the other hand, AlbCre+/caNrf2+ that underwent IR had significantly reduced serum transaminases, less necrosis on histology, and a less pronounced inflammatory infiltrate and inflammatory cytokine expression as compared to the littermate controls. However, there were no differences in apoptosis. Taken together, Nrf2 plays a critical role in our murine model of warm hepatic IRI, with Nrf2 deficiency exacerbating hepatic IRI and hepatocyte‐specific Nrf2 overactivation providing protection against warm hepatic IRI. Liver Transpl 22:91‐102, 2016 . © 2015 AASLD.